Characteristics of the Shrinkage Behavior on the Peaty Soils: Studies on the farm land improvement of peaty bog in low area (I) - YABASHI, Shingo (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1980)
There is an extensive distribution of peaty soils in the West Tsugaru district in Aomori Prefecture. In this district, peaty soils must be used as base farm land. Since the shrinkage and the compressibility of peaty soils are quite considerable, the properties of these soils must be improved. Peaty soils are divided into three types Root Mat, Peat and Muck. The author investigated the shrinkage behavior of these three soils. Their shrinkage characteristies are given as follows: (1) Root Mat: Ratio of shrinkage is smaller than those of Peat and Muck. Structural shrinkage begins at pF 1.1 and it's range is a somewhat long. There is almost no normal shrinkage. Residual shrinkage begins at pF 4.4 and this stage is very long. (2) Peat: Ratio of shrinkage is large. The stage of structural shrinkage shows shrinkage at the outset and the period of time for shrinkage is neither very long nor short. Normal shrinkage can be observed from pF 2.3 to pF 4.1 and it's range is a somewhat long. Residual shrinkage begins at pF 4.1 and the stage is short. (3) Muck: Ratio of shrinkage is large. Normal shrinkage begins at the first stage of shrinkage and continues up at to pF 3.0. Structural shrinkage appears slightly after pF 3.O. Residual shrinkage begins at pF 4.3 and it's range is very short.